Postoperative Radiotherapy in Locally Invasive Malignancies of the Thymus: Patterns of Care and Survival. Issue 12 (December 2016) - Boothe, Dustin; Orton, Andrew; Thorpe, Cameron; Kokeny, Kristine; Hitchcock, Ying J.
ABSTRACT : Introduction: : Our purpose was to determine the overall survival (OS) benefit of postoperative radiotherapy (PORT) in patients with advanced thymic malignancies and the associated predictors of PORT receipt. Methods: : We queried the National Cancer Data Base for all stage II to III thymic malignancies. Trends in PORT use over time were analyzed using least squares linear regression. Factors predictive of PORT and OS were identified by using multivariate logistic and Cox regression analysis, respectively. Results: : We identified 1156 patients between 2004 and 2012 who met the inclusion criteria. The utilization of PORT was found to increase over the study period by 41% (37% to 52% [ p = 0.01]). On multivariate analysis, the factors found to be the most predictive of receipt of PORT were positive surgical margins (adjusted OR = 1.98 [ p < 0.01]) and treatment at a nonacademic facility (adjusted OR = 1.44 [ p = 0.01]). The 5‐year OS was superior for patients receiving PORT compared with for those who did not (83% versus 79%, p = 0.03). Receipt of PORT was associated with a trend toward decreased risk for death on multivariate analysis (hazard ratio = 0.75 [ p = 0.09]). In addition, a positive macroscopic margin was the most important predictor of survival (hazard ratio = 3.48 [ p < 0.01]). On subgroup analysis, patients with thymic carcinoma and WHO histologic types A and AB were associated with an OS benefit with PORT, whereas types B1, B2, and B3 were not. Patients with positive margins were not associated with an OS benefit with PORT. Conclusions: : The use of PORT in patients with advanced thymic malignancies is increasing over time and is determined by both clinical and demographic factors. Receipt of PORT was associated with improved OS. The OS benefit with PORT was dependent on the WHO histologic type.